2017
DOI: 10.1371/journal.pone.0179809
|View full text |Cite
|
Sign up to set email alerts
|

Selective cyclooxygenase inhibition by SC-560 improves hepatopulmonary syndrome in cirrhotic rats

Abstract: ObjectiveHepatopulmonary syndrome (HPS) is characterized by hypoxia in patients with chronic liver disease. The mechanism of HPS includes pulmonary vasodilatation, inflammation, and angiogenesis. Prostaglandins synthesized by cyclooxygenases (COX) participate in vascular responsiveness, inflammation and angiogenesis, which can be modulated by COX inhibitors. We therefore evaluated the impact of COX inhibition in rats with common bile duct ligation (CBDL)-induced liver cirrhosis and HPS.MethodsCirrhotic rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…COX-1 is involved in the regulation of angiogenesis, positively correlated with the expression of VEGF, while inhibition of COX-1 can reverse this relevance [21]. SC-560 can inhibit tumor angiogenesis by inhibiting COX-1 expression [11], the pivotal mechanism is related to decrease tumor-associated VEGF expression [20,22] and the expression of MDR1 P-glycoprotein (Pgp). The VEGF mRNA expression level in SC-560 group was significantly suppressed, which was different from the control group in present study.There were synergistic repressions on expression of VEGF mRNA in SC-560 + DDP and SC-560 + taxol group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COX-1 is involved in the regulation of angiogenesis, positively correlated with the expression of VEGF, while inhibition of COX-1 can reverse this relevance [21]. SC-560 can inhibit tumor angiogenesis by inhibiting COX-1 expression [11], the pivotal mechanism is related to decrease tumor-associated VEGF expression [20,22] and the expression of MDR1 P-glycoprotein (Pgp). The VEGF mRNA expression level in SC-560 group was significantly suppressed, which was different from the control group in present study.There were synergistic repressions on expression of VEGF mRNA in SC-560 + DDP and SC-560 + taxol group.…”
Section: Discussionmentioning
confidence: 99%
“…The VEGF mRNA expression level in SC-560 group was significantly suppressed, which was different from the control group in present study.There were synergistic repressions on expression of VEGF mRNA in SC-560 + DDP and SC-560 + taxol group. Chang et al [22] found that SC-560 attenuated angiogenesis by downregulating COX-, nuclear factor kappa B-and VEGF-mediated pathways, and improved hepatopulmonary syndrome in cirrhotic rats. A previous report [23] also suggested that ximenynic acid (COX-1-selective inhibitor) reduced the expression level of VEGF-B and VEGF-C.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 Thus, the COX-1-selective inhibitor SC-560, a diarylpyrazole analog, was discovered via the deletion of the sulfonamide group from celecoxib. 30 SC-560 has been extensively used as an in vivo probe for COX-1’s involvement in biological responses; 31 , 32 however, when [ 11 C]SC-560 was synthesized for PET imaging, COX-1-dependent accumulation in tissues could not be demonstrated. 33 This failure is likely because SC-560 has not been optimized for in vivo activity and suffers from multiple liabilities, including poor solubility and pyrazole-associated off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…The diarylheterocyclic scaffolds yielded the highest number of potent and selective COX-2 inhibitors, such as celecoxib, rofecoxib, and valdecoxib (Figure a) . The key determinant of the COX-2 selectivity of these compounds is the presence on one of the aromatic rings of a sulfonamide or a methylsulfone that inserts into a side-pocket in the cyclooxygenase active site that is only accessible in COX-2. , Thus, the COX-1-selective inhibitor SC-560, a diarylpyrazole analog, was discovered via the deletion of the sulfonamide group from celecoxib . SC-560 has been extensively used as an in vivo probe for COX-1’s involvement in biological responses; , however, when [ 11 C]­SC-560 was synthesized for PET imaging, COX-1-dependent accumulation in tissues could not be demonstrated .…”
Section: Discussionmentioning
confidence: 99%
“…This was an important observation since PPAR-γ activation inhibits the expression of several inflammatory response genes, including those of TNF-α and COX-2 [18]. Further, COX-2 was activated following the mobilization of NF-κB signaling in the BDL rat model, and decreased expression of both COX-2 and NF-κB, and thus attenuated inflammation in the BDL-induced rat model [20,21]. Thus, in the present study, we suggest that the protective effect of SFI might be due to inhibition of COX-2 and NF-κB expression by a mechanism that might be partly dependent on up-regulated functional expression of PPAR-γ.…”
Section: Discussionmentioning
confidence: 99%